Tagar #IndonesiaGelap Sebagai Cerminan Disorganisasi Sosial Politik: Studi Kasus Aksi Mahasiswa 2025 (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
The viral phenomenon of #IndonesiaGelap on social media in early 2025 reflects symptoms of socio-political disorganization in Indonesia. This hashtag symbolizes public and student unrest concerning the crisis of institutional legitimacy, weakened regulatory functions, and the erosion of public trust. This study uses a qualitative approach with a case study method, focusing on student protests at Universitas Negeri Jakarta (UNJ) as a response to perceived political injustice. Using the framework of structural functionalism and Émile Durkheim’s concept of anomie, the movement is interpreted as an adaptive response to systemic failure in providing legitimate channels for justice and democracy. Although it has not resulted in direct policy change, the movement has raised collective awareness, expanded public discourse, and reaffirmed the role of students as agents of change in the digital age. The study recommends collaboration among students, government, and civil society to create a more inclusive and responsive socio-political system.